The Results Framework of the Agenda 2030 for Sustainable Development and the Ebbs and Flows of International Development - Oladele, Aderemi (Technium Sustainability, 2022)
By vision and design, the Agenda 2030 for Sustainable Development carries two integrated and distinct features, identified as both challenge and opportunity in international development. These are notably its game-changing “results framework” and an objective to “leave no one behind” - a political imperative linked to the concept of universality, which tends to close the margin between developing and developed countries in the agenda’s applicability. These features do not only respond to change in approach to international development action for greater effectiveness, they also offer avenues for studies into susceptible changes in the perception of certain established concepts and rudiments, including those linked to reforms in global governance, management and Africa’s specificity. Through a qualitative analysis of selected contemporary debates around the Agenda 2030, this essay aims to underscore some possible alterations to perceptions of international development within the framework of the Agenda 2030 for sustainable development. To further illustrate the results framework and universality of the SDG’s examples were explored to highlight particularly implications for Africa as a development priority region.